Age-associated alterations in immune and inflammatory responses in captive olive baboons (Papio anubis) - Mulholland, Michele M.; Nehete, Bharti P.; DeLise, Ashley; Achorn, Angela M.; Pytka, Lisa M.; Nehete, Pramod N. (Frontiers in Aging, 2025)
IntroductionAdvanced age is a primary risk factor for many chronic diseases and conditions; however, age-related immune dysregulation is not well understood. Animal models, particularly those that resemble human age-related physiological changes, are needed to better understand immunosenescence and to improve health outcomes. Here, we explore the utility of the olive baboon (Papio anubis) in studying age-related changes to the immune system and understanding mechanisms of immunosenescence.MethodsWe examined immune cell, inflammatory responses, cytokines, and cortisol levels using hematology and flow cytometry, mitogen stimulation, multiplex cytokine assay, and cortisol immunoassay.Results and DiscussionOur results reveal significant age effects on numerous immune and inflammatory responses. For instance, adult and aged monkeys exhibited significantly fewer monocytes than young monkeys. After stimulation with Con A and PWM (separately), we found that old baboons had higher INFγ expression compared to young baboons. Similarly, after stimulation with LPS and PWM (separately), we found that old baboons had higher TNFα expression compared to young baboons. These findings suggest that the olive baboon is a suitable model for biogerontology research, immune senescence, and development of vaccines. Though there are phenotypic and functional similarities between baboons and humans, specific differences exist in immune cell expression and immune function of lymphocytes that should be considered for better experimental outcomes in the development of therapeutics and restoring innate and adaptive immune function in aged individuals.